Role of Linguistic Similarity in the Acquisition of Imperative Request form by Urdu Punjabi Simultaneous Bilinguals: A Study of Bilingual Children Living in Lahore, Pakistan (Al-Qamar, 2021)
The aim of this research paper is to find out the role of linguistic similarity in the acquisition of imperative request form in Urdu Punjabi simultaneous bilingual children living in Lahore, Pakistan. The hypothesis for this work adopted was whether the linguistic similarity accelerates or delays the acquisition process in these sister languages. 36 simultaneous bilinguals from 3.0-6.0 years divided into 6 groups age wise speaking Urdu and Majhi dialect of Punjabi in Lahore were interviewed and their responses were recorded. Across the group and across the language analysis was done. The results indicated that bilingual children showed the acquisition of imperative request form in both the languages during the same time period i.e. 3.5-4.0 which pointed out that the correlation between the languages facilitated the acquisition process.
Keywords: Imperative request form; simultaneous bilinguals